The Theme of Magic in Florentine Picture-Chronicle Drawings (British Museum, London): Motifs, Textual and Iconographic Origins - Piven, Marina G. (Actual Problems of Theory and History of Art, 2023)
The study aims to investigate the drawings of the Florentine Picture Chronicle (c. 1470–1475, British Museum, London) dedicated to the motifs of magic. The authorship of that book of drawings is associated with the circle of Maso Finiguerra and Baccio Baldini. The content of the album is based on a general program that represents world history in visual images. The theme of magic within the compositions of the “Florentine Chronicle” is an important semantic line. Its pages contain the collected figures of Zoroaster, Ostanes, and Hermes Trismegistus, as well as many characters of Greco-Roman mythology and the Old Testament, who appear in the light of their possession of secret knowledge. The article considers the iconographic prototypes of the drawings and analyzes the literary texts that influenced the choice and determined the pictorial interpretation of the characters. Special attention has been paid to the historical and cultural context of life in 15th-century Italy, which sparked an interest in the theme of magic in art.
Keywords: Picture-Chronicles manuscripts; Florentine Chronicle; Maso Finiguerra; Baccio Baldini; motifs of magic in Renaissance art